2021
DOI: 10.1155/2021/9928284
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition, Relative Abundance, and Habitat Association of Avifauna in Zegie Peninsula Forest Patches and Associated Wetlands, Bahir Dar, Ethiopia

Abstract: Introduction. Ethiopia is one of the most avifauna rich countries in Africa. Avifaunal surveys are required to inform conservation decisions and enhance land management for biodiversity. Avifaunal surveys from Ethiopia are lacking. This study examines species composition, relative abundance, and habitat association of avian fauna in Zegie Peninsula forest patches and associated wetlands from surveys carried out from August 2018 to March 2019, covering both the wet and dry seasons. Data Collection. Forest, shru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…A study supported by Tsegaye et al [26], indicated that diferences in species diversity, species abundance, and number of individuals among diferent species were associated with diferences in habitat characteristics and feeding habits. In addition, Mola et al [36] reported that the distribution and abundance of many bird species is determined by the vegetation structure. [30,37] say that the lowest species richness and abundance were observed in forest habitats than in farms and settlements.…”
Section: Discussionmentioning
confidence: 99%
“…A study supported by Tsegaye et al [26], indicated that diferences in species diversity, species abundance, and number of individuals among diferent species were associated with diferences in habitat characteristics and feeding habits. In addition, Mola et al [36] reported that the distribution and abundance of many bird species is determined by the vegetation structure. [30,37] say that the lowest species richness and abundance were observed in forest habitats than in farms and settlements.…”
Section: Discussionmentioning
confidence: 99%
“…Avian diversity of wetlands in Bahir dar, Ethiopia was determined during wet and dry seasons. The eld survey identi ed 96 species of birds in which 40 species were observed in wet season, 13 species in dry season while 43 species were common at both seasons (Mola, 2021). During the year around survey 2550219 individuals from 55 species of birds were reported.…”
Section: Discussionmentioning
confidence: 99%
“…By following Mola et al (2021) Line transect method was used for observing the birds of wetland area of Thal desert. Since Thal desert contains uniform type of habitat due to very little vegetation, birds are easily visible.…”
Section: Field Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The possible random blocks were selected for natural, plantation, and farmland habitats. As shown in table (8), below a grid to each habitat consisting of 0.5x1km cells was applied [60]. Then random blocks were selected, resulting in 24 blocks in the natural forest, 10 in the plantation forest, and 10 in the farmlands based on the size of habitats [59].…”
Section: Sampling Designmentioning
confidence: 99%